Comprehensive mutation scanning of KCNQ1 in 111 Han Chinese patients with lone atrial fibrillation. Issue 1 (8th November 2010) - Chen, Lin Y; Goh, June M; Wong, Raymond C; Hsu, Li-Fern; Foo, David; Benditt, David G; Ling, Lieng H; Heng, Chew K
Abstract : Objective: To determine the extent to which genetic variation in the potassium channel gene KCNQ1 causes atrial fibrillation (AF). Design: Case–control study. Setting: National University Hospital, Singapore. Patients: Han Chinese patients (n=111) with lone AF (onset <60 years and lacking risk factors) and 265 Han Chinese controls. Interventions: Blood draw, 12-lead electrocardiogram and transthoracic echocardiogram were performed on patients with AF at enrolment. Main outcome measures: DNA sequence variants in the coding region and exon–intron boundaries of KCNQ1 as detected by direct sequencing. Results: Four previously reported coding variants were identified: I145I, S546S, P448R and G643S. An additional 19 non-coding variants were identified, nine of which are newly reported. None were predicted to create a cryptic splicing site. The allele frequencies of the two non-synonymous variants did not differ significantly in the AF cases compared with 265 Han Chinese controls (P448R: 10.8% in cases vs 8.6% in controls, p=0.41; G643S: 1.4% in cases vs 0.8% in controls, p=0.43). Conclusions: Comprehensive mutation scanning of KCNQ1 did not identify novel pathogenic mutations or risk-conferring polymorphisms. As in Caucasians, genetic variation in KCNQ1 is not a common cause of AF in Han Chinese. Routine genetic testing of KCNQ1 for AF is, therefore, not warranted.